2020
DOI: 10.1111/bdi.12943
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the later stage of bipolar disorder: Descriptive analyses from the ORBIT trial

Abstract: Objectives This study aimed to investigate the features of later stage bipolar disorder (BD) and specifically, factors underlying later stage BD and potential subgroups within this stage, to understand more about the later stage group and contribute to the measurement of stage. Methods An exploratory factor analysis was conducted using variables relating to current phenomenological aspects of illness, followed by cluster analyses based on the identified factors. Finally, the resultant clusters were compared ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For example, an early trial of CBT for bipolar disorder (Scott et al, 2006) found a bifurcation at 12 episodes: adjunctive CBT was superior to treatment as usual in participants with fewer than 12 previous episodes, but less effective in those with more episodes. Much remains unknown about treatment implications of the long-term trajectory of bipolar disorder (Tremain et al, 2019, 2020a), but clinicians should be mindful of the additional challenges likely to confront patients with a long history of relapses, growing chronicity and psychosocial challenges. In some cases, living well despite ongoing symptoms may be a reasonable goal, and the focus of psychological work may shift to values-based and self-compassion work (Murray et al, 2017).…”
Section: Management Of Bipolar Disordermentioning
confidence: 99%
“…For example, an early trial of CBT for bipolar disorder (Scott et al, 2006) found a bifurcation at 12 episodes: adjunctive CBT was superior to treatment as usual in participants with fewer than 12 previous episodes, but less effective in those with more episodes. Much remains unknown about treatment implications of the long-term trajectory of bipolar disorder (Tremain et al, 2019, 2020a), but clinicians should be mindful of the additional challenges likely to confront patients with a long history of relapses, growing chronicity and psychosocial challenges. In some cases, living well despite ongoing symptoms may be a reasonable goal, and the focus of psychological work may shift to values-based and self-compassion work (Murray et al, 2017).…”
Section: Management Of Bipolar Disordermentioning
confidence: 99%